Incremental Value of Preoperative Copeptin for Predicting Myocardial Injury. (December 2016) - Mauermann, Eckhard; Bolliger, Daniel; Seeberger, Esther; Puelacher, Christian; Corbiere, Sydney; Filipovic, Miodrag; Seeberger, Manfred; Mueller, Christian; Lurati Buse, Giovanna
Abstract : BACKGROUND: Copeptin, a novel marker of endogenous stress, has shown diagnostic and prognostic value in nonsurgical patients with a suspected coronary event. We aimed to assess the incremental value of copeptin in addition to established preoperative risk indices to predict the occurrence of postoperative myocardial injury. METHODS: This secondary analysis of prospectively collected data included adults undergoing noncardiac surgery with risk factors for adverse perioperative cardiac events based on preoperative risk stratification. We examined preoperative copeptin in patients without elevated preoperative troponin and its association with myocardial injury by receiver operator characteristic curves, logistic regression, and net reassignment indices. RESULTS: Of the 190 patients included, 33 (17.4%) experienced myocardial injury within 48 hours, and 17 (8.9%) experienced cardiac death and/or major adverse cardiac events within the first postoperative year. Preoperative copeptin showed an area under the receiver operator characteristic curve of .66 (95% confidence interval, .55–.76) for myocardial injury and an optimal cutoff of 9.6 pmol/L. This cutoff was an independent predictor of myocardial injury, with an odds ratio of 4.67 (95% confidence interval, 2.06–11.19) when adjusted for age, sex, and the revised cardiac risk index. The net reassignment improvement for myocardial injury was between 39% and 50% for both events and nonevents when adding copeptin to established preoperative risk indices. No significant difference in major adverse cardiac event and/or cardiac death was observed. CONCLUSIONS: Copeptin (≥9.6 pmol/L) was associated with significantly higher rates of myocardial injury and improved risk stratification in patients scheduled for noncardiac surgery with nonelevated preoperative troponin. Abstract : Supplemental Digital Content is available in the text.